Vertical distribution and respiration rates of benthic foraminifera: Contribution to aerobic remineralization in intertidal mudflats covered by Zostera noltei meadows. (20th September 2016) - Cesbron, F.; Geslin, E.; Jorissen, F.J.; Delgard, M.L.; Charrieau, L.; Deflandre, B.; Jézéquel, D.; Anschutz, P.; Metzger, E.
Abstract: The present study investigates the influence of seagrass root systems on benthic hard-shelled meiofauna (foraminifera). In February and July 2011, sediment cores were collected at low tide at two sites in Arcachon lagoon, a vegetated site with Zostera noltei and a second site with bare sediments. We used the highly discriminative CellTracker™ Green fluorogenic probe technique to recognize living foraminifera and to describe foraminiferal density and diversity. Three dominant species of foraminifera were observed: Ammonia tepida, Haynesina germanica and Eggerella scabra . The two calcareous species, A. tepida and H. germanica, were preferentially found in the upper half to 1 cm of the sediment. At the vegetated site, these two species had a slightly deeper microhabitat. In the literature, both species have been described alive in much deeper sediment layers, possibly due to false positives from the Rose Bengal staining method. These two species also showed 1) higher densities at the site with Z. noltei, 2) a higher density in February when conditions were supposed optimal due to a microphytobenthos bloom, and 3) dissolved calcitic shells in July, probably resulting from a lower pH. The agglutinated species E. scabra was present alive down to at least 7 cm depth. E. scabra showed high densities in the anoxic part of the sediment at both the vegetated and bare sites, with a substantially higher density in summer at the site with bare sediments. Its presence at depth may be related to its trophic requirements; this species could be less dependent on labile organic matter than A. tepida and H. germanica . On this intertidal mudflat, the foraminiferal contribution to aerobic carbon remineralization, based on respiration rate measurements, can account for up to 7% of the diffusive oxygen uptake, almost five times more than the maximum contribution recorded in open marine environments (300 m depth) in the Bay of Biscay. Graphical abstract: Highlights: Ammonia tepida and Haynesina germanica were found alive mainly in the 0–0.5 cm depth interval. These two species were found alive in the 0.5–1 cm depth at the vegetated site. Important dissolution of calcareous specimens was observed in July. Eggerella scabra was observed all along the cores, down to 7 cm depth. Foraminiferal species were responsible for up to 7% of the total Diffusive Oxygen Uptake.